Mesin Pengiris Ubi Mengunakan TIMER - Yanie, Ahmad; Roza, Indra; Tumanggor, Daniel; Rzk, M Fathur; Sihotang, Chirstian (LPPM STIKOM Tunas Bangsa, 2024)
Nowadays technology has developed rapidly, many electronic devices have been created to help or make human work easier. This can be seen in developments at the beginning of the 21st century where humans have been able to create communication devices that do not use cables, such as cell phones, and also computers that are packaged and made so that they can be carried by users, such as laptops. Likewise with industrial equipment as well as home industrial equipment such as equipment for separating or roasting coffee and also automatic coffee drying equipment. One piece of equipment that is no less popular for housewives and home businesses is equipment for cutting cassava. The design of an automatic cassava cutting tool is useful for helping home industry activities. Just put the cassava in the tube and automatically the motor connected to the cutting knife will rotate and will automatically stop at the predetermined timer.